Evaluation of quality properties and antioxidant activities of tiger nut (Cyperus esculentus L.) oil produced by mechanical expression or/with critical fluid extraction. (April 2021) - Guo, Tingting; Wan, Chuyun; Huang, Fenghong; Wei, Chunlei
Abstract: The quality properties and antioxidant activities of tiger nut ( Cyperus esculentus L.) oil produced using mechanical expression with subcritical n -butane extraction (ME-SBE) and supercritical CO2 extraction (ME-SCO2 E) were investigated and compared with mechanical expression or critical fluid extraction. Results showed that the highest extraction yield was obtained by ME-SBE (28.47 ± 0.20 g/100 g) and ME-SCO2 E (28.56 ± 0.24 g/100 g). The content of tocopherols, β -carotene and total phenolic compound in oil extracted by ME-SBE (30.69 ± 0.15 mg/100 g, 160.56 ± 7.98 μg/100 g and 28.79 ± 0.34 mg sinapic acid/100 g, respectively) were the highest, and followed by ME-SCO2 E oil, For fatty acid composition, five oils were similar and rich in oleic acid (73.81–74.10%) and linoleic acid (8.75–8.89%). Furthermore, oil extracted by ME-SBE presented the uppermost antioxidant activities and oxidation stability, which were correlated with α-tocopherols, total tocopherols and total phenolic compound content. Thus, mechanical expression with subcritical n -butane extraction appeared to be preferable for tiger nut oil extraction. Highlights: Profiles of tiger nut oils obtained by five methods were studied. ME-SBE was proven to be the most suitable method, and the highest yield was 28.5 g/100 g Tiger nut oils showed a predominance of oleic acid (73.81–74.10%). Oil extracted by ME-SBE appeared better qualities and antioxidant activities.